Caries risk factors among children aged 3-5 years old in Indonesia - Sri Ratna Laksmiastuti; Tri Erri Astoeti; Heriandi Sutadi; Sarworini B Budiardjo (Wolters Kluwer Medknow Publications, 2019)
Background: Dental caries is the most common oral disease in children. Dental caries is a multifactorial disease both etiologic factor and risk factor. Other factors that could not find in clinical examination or radiograph, but contribute to the disease are assumed as risk factor. A child as an un independent individual will be influenced by external risk factor, especially from the mother. Mother is an important figure for children character building. Risk factor detection is an essential effort to decrease the prevalence of dental caries. Aim: The aim of this study is to identify caries risk factor in children aged 3-5 years old in Indonesia. Setting and Design: A descriptive, cross-sectional study was conducted using a universal sampling protocol. Methods: Subject is 248 pairs of mother and children. Clinical examination and questionnaire interview are applied on the subject. Statistical Analysis: The association between caries risk factors and caries cases on children were tested using bivariate analysis, followed by identifying the most dominant factors using logistic regression multivariate analysis. Results: Each caries risk factor has a significance level which could distinct to children's caries case. After multivariate logistic regression, maternal attitude and how to drink milk bottle were the most risk factors to childhood caries (odds ratio: 3.61; 95% confidence interval [CI]: 1.18-11.01 and 7.69; 95% CI: 1.84-32.13 respecting). Conclusions: Many risk factors contribute to childhood caries, originated from both children themselves and mothers. Caries risk factor identification is an important role in preventing childhood caries.